Understanding patients' preferences for treatment: the need for innovative methodologies. (1st September 2001) - Frewer, L J; Salter, B; Lambert, N
Abstract : Treatment selection is now much more consumer driven than in the past. However, there is a need to develop investigative methodological approaches that are sensitive to differences in patient preferences if full account is to be taken of what the patient sees as the best option in terms of different possible treatments available for a particular condition. Previous attitude research has been criticised because it does not provide insight into reasons why people hold different preferences or beliefs. A methodology is described which allows people to describe their concerns and values associated with different treatment options in their own words. This is the repertory grid method of eliciting personal constructs used in conjunction with generalised Procrustes analysis (GPA). An example of the use of this methodology is provided, drawn from research directed towards understanding people's beliefs about genetic technologies. A possible application of the method to understanding treatment preferences related to type 2 diabetes is also discussed. It is concluded that the use of innovative methodologies is essential if our understanding of patient preferences regarding treatment options is to have a significant impact on patient quality of life.